2023
DOI: 10.3390/microorganisms11092168
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Response of Rhodosporidium kratochvilovae to Glucose Starvation: A Transcriptomics-Based Analysis

Meixia He,
Rui Guo,
Gongshui Chen
et al.

Abstract: Microorganisms adopt diverse mechanisms to adapt to fluctuations of nutrients. Glucose is the preferred carbon and energy source for yeast. Yeast cells have developed many strategies to protect themselves from the negative impact of glucose starvation. Studies have indicated a significant increase of carotenoids in red yeast under glucose starvation. However, their regulatory mechanism is still unclear. In this study, we investigated the regulatory mechanism of carotenoid biosynthesis in Rhodosporidium kratoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 78 publications
1
0
0
Order By: Relevance
“…Studies have suggested that there is a correlation between elevated carotenoid levels and reduced lipid biosynthetic flux [32]. Our previous data also suggested a positive correlation between fatty acid degradation and carotenoid biosynthesis in Rhodosporidium kratochvilovae [58]. This study further reinforced the notions by demonstrating a reduction in lipid content (Figure 3b) resulting from the regulation of key genes expressed that were involved in lipid biosynthesis and the fatty acid β-oxidation.…”
Section: Discussionsupporting
confidence: 80%
“…Studies have suggested that there is a correlation between elevated carotenoid levels and reduced lipid biosynthetic flux [32]. Our previous data also suggested a positive correlation between fatty acid degradation and carotenoid biosynthesis in Rhodosporidium kratochvilovae [58]. This study further reinforced the notions by demonstrating a reduction in lipid content (Figure 3b) resulting from the regulation of key genes expressed that were involved in lipid biosynthesis and the fatty acid β-oxidation.…”
Section: Discussionsupporting
confidence: 80%